Reproductive success and compatibility among accessions of Jatropha curcas in Indonesia - Palupi, Endah R.; Ahmad, Ade S.; Affandi, Rofiq; Qadir, Abdul; Randriani, Eni (Journal of Tropical Crop Science, 2014)
Large scale exploitation of Jatropha curcas for biofuelproduction is restrained by low productivity henceeconomically not protable. One of the main constraintsis due to limited number of female owers in aninorescence which eventually develop into fruits thatbear seed. Investigation on oral biology andreproductive potential of the species had been carriedout, but seems to vary among sites. The research wasconducted to study reproductive success and thecompatibility among Indonesian Jatropha accessions.The research was set up in two experiments. The rstexperiment was conducted at the Jatropha seedorchard, Pakuwon, Sukabumi, West Java from April toJuly 2007 using four-year- old trees of accessions fromLampung, Banten, West Java, and Central Java. Thesecond experiment was conducted at LeuwikopoExperimental Station of Bogor Agricultural Universityfrom April to July 2008 using one-year-old trees ofaccessions from Lampung, Bengkulu, Palembang, andKediri. Flowers were obtained from controlled self andcross-pollinated as well as left for open-pollination. Theresult showed that reproductive success varied amongaccessions; the greatest success was 0.73 obtainedfrom aWest Java accession and the least was 0.53 fromBanten accession. The Jatropha accessions werecategorized as partially self-incompatible as indicatedby index of self-incompatibility (ISI) that ranged 0.93-0.99. Banten accession produced highly viable andvigorous seeds regardless of pollination methods;accessions of Central Java produced higher viabilityseeds when cross-pollinated within accession, whereasthose from West Java and Lampung produced higherviability seeds when self-pollinated.Keywords: accessions, Jatropha curcas, selfpollination,self-incompatibility, seedviability